(untitled) (Bangladesh Journal of Neuroscience, 2013)
Objective: To identify the common risk factors associated with carpal tunnel syndrome. Methodology:This case-control observational study was conducted in the department of neurology and medicine, DMCH from May 2010 to April 2011 for a duration of 1 year. The study included purposively selected 80 persons. Patients attending the outdoor and admitted in indoor of department of neurology and medicine, DMCH with a clinically suspected CTS and established by electrophysiological parameters selected as cases (group –I) . Healthy volunteers and subjects who were devoid of any features of CTS but having history with isolated injury to the lower limb nerve and isolated facial nerve palsy with normal electrophysiological parameters selected as control (group –II). Data were collected by interview of the patients, clinical examination and laboratory investigations using the research instrument. Result: The mean age was 42.7±9.8 years with range from 24 to 64 years and 41.1±9.1 years with range from 26 to 61 years in group-I and group-II respectively. The proportion of male and female patients was similar in both the study groups. Male Female ratio was 1: 7 in both groups. In this study it was observed that hypothyroidism was found 25.0% in group I and 5.0% in group II, which was significantly (p<0.05) higher in carpal tunnel syndrome patients. Diabetes mellitus was significantly higher in carpal tunnel syndrome patients, which was 22.5% in group I and 7.5% in group II. Rheumatoid arthritis was found 20.0% in group I and 5.0% in group II, which was significantly (p<0.05) higher in patients with carpal tunnel syndrome. Pregnancy was found 11.4% in group I and 2.9% in group II. CKD with hemodialysis was found 17.5% and 7.5% in group I and group II respectively. In pregnancy and CKD with hemodialysis difference was not statistically significant (p>0.05) among the two groups. Regarding obesity it was found in this present series that 42.5% and 17.5% patients were obese in group I and group II respectively. Obesity was significantly (p<0.05) higher in patients with carpal tunnel syndrome. In this study it was found in multivariate analysis that patients with hypothyroidism 1.28 times, DM 2.20 times, RA disease 3.84 times, obesity 5.9 times more likely to be associated with carpal tunnel syndrome but CKD with hemodialysis patients and pregnancy were not significantly associated in multivariate analysis. In this study it was also found that almost a half (47.5%) of the patients was housewives followed by garment workers (27.5%) and clerical workers (22.5%) in group I, which indicates that carpal tunnel syndrome was more common among housewives. Conclusion: A conclusion can be made from the above mentioned result that CTS is multifactorial. Obesity, diabetes mellitus, hypothyroidism and rheumatoid arthritis are commonly associated with carpal tunnel syndrome. Moreover female sex and age were also associated with CTS. This study also found that patients diagnosed as having work-related CTS have a high prevalence of concurrent medical conditions capable of causing CTS without respect to any particular occupation. Bangladesh Journal of Neuroscience 2013; Vol. 29 (2) : 70-78